2011
DOI: 10.1016/j.yhbeh.2011.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of suppressing gonadal hormones on response to novel objects in adolescent rats

Abstract: Human adolescents exhibit higher levels of novelty-seeking behaviour than younger or older individuals, and novelty-seeking is higher in males than females from adolescence onwards. Gonadal hormones, such as testosterone and estradiol, have been suggested to underlie age and sex difference in response to novelty; however, empirical evidence in support of this hypothesis is limited. Here, we investigated whether suppressing gonadal hormone levels during adolescence affects response to novelty in laboratory rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…The current findings add further support to those assertions that developmental exposure to EDCs creates sex-specific alterations in exploratory behavior (Patisaul, Sullivan, 2012). In this study, vehicle males showed significantly increased overall exploration time with objects compared to vehicle females, findings consistent with prior reports (Cummings et al, 2013, Cyrenne and Brown, 2011, Frick and Gresack, 2003, Wilson and Daly, 1985). In contrast, mice developmentally exposed to the mixture of EDCs showed the opposite relationship, as MIX exposed males showed significantly decreased exploration times compared to MIX exposed females.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current findings add further support to those assertions that developmental exposure to EDCs creates sex-specific alterations in exploratory behavior (Patisaul, Sullivan, 2012). In this study, vehicle males showed significantly increased overall exploration time with objects compared to vehicle females, findings consistent with prior reports (Cummings et al, 2013, Cyrenne and Brown, 2011, Frick and Gresack, 2003, Wilson and Daly, 1985). In contrast, mice developmentally exposed to the mixture of EDCs showed the opposite relationship, as MIX exposed males showed significantly decreased exploration times compared to MIX exposed females.…”
Section: Discussionsupporting
confidence: 93%
“…There is experimental evidence that such behavioral differences can be hormonally mediated, as rats exposed to a long-acting gonadotrophin-releasing hormone antagonist, Antide, demonstrated a similar behavioral reversal. Antide treated males showed reduced serum testosterone and diminished preference for novelty compared to females (Cyrenne and Brown, 2011). Additionally, gonadectomized males showed diminished exploratory behavior compared to control males, while gonadectomized males given testosterone increased novel object exploration (Aubele et al, 2008b).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…While no sex differences in novelty-seeking were observed at any age in this [38] and similar studies examining response to novelty [36], other studies have reported adult male mice [39] and adolescent and adult male rats [40] to show greater preferences for novel objects than adult females. Indeed, increases in gonadal hormones associated with puberty have been suggested to underlie age- and sex-typical responses to novelty, a suggestion supported by data showing that long-term suppression of gonadal hormone production via prepubertal administration of Antide eliminated sex differences in novelty preference during late adolescence [41]. Yet, groups of similarly treated adults were not included in this study, and thus it is unclear whether the observed effects were related to activational or organizational effects of gonadal hormones.…”
Section: Introductionmentioning
confidence: 99%
“…Avoidance or fear of novelty (i.e., neophobia) is also suggested to be influenced by gonadal hormone levels in mammals (Cornwell-Jones & Kovanic 1981). For example, novelty-seeking behavior was reduced by suppressing gonadal hormone levels in rats (Cyrenne & Brown 2011). By contrast, the approach taken in many avian studies has mainly focused on the long-term effects of maternal steroids in behavioral responses to novelty.…”
Section: Shammentioning
confidence: 99%